A Differentiated View on Short Stemmed Hip Arthroplasty – What are the Differences in Fixation and Biomechanics? - Jerosch, Jörg; von Engelhardt, Lars Victor (Zeitschrift für Orthopädie und Unfallchirurgie, 2019)
The present paper gives an overview of the different types of short stem total hip replacements. There is a pronounced inhomogeneity of the nomenclature in clinical practice as well as in regard to the scientific literature. Examples include neck preserving implants, meta-, epi- or metadiaphyseal fixed implants, microimplants, ultrashort implants, partial neck preserving implants, trochanteric sparing implants, implants with extra- and/or intramedullar fixation, implants without primary fixation, etc. Biomechanically, the short stems vary from very short, completely neck retaining versions up to implants which are just a shorter version of a standard implant. A frequently cited classification recommends the osteotomy level as a discriminating factor. This classification categorizes into a neck preserving, partial neck preserving and neck resecting short stems.Die vorliegende Arbeit gibt eine Übersicht über die verschiedenen Kurzschaftendoprothesen des Hüftgelenkes. Im klinischen Alltag und in der wissenschaftlichen Literatur findet sich jedoch eine große Inhomogenität bei der Nomenklatur. Es finden sich Begrifflichkeiten wie schenkelhalserhaltende Prothesen, meta-, epi- oder metadiaphysär verankerte Prothesen, Mikroprothesen, ultrakurze Schäfte, Schenkelhalsprothesen, Teilschenkelhalsprothesen, trochantererhaltende Prothesen, Prothesen mit extra- und/oder intramedullärer Abstützung sowie Prothesen ohne Abstützung etc. Biomechanisch reichen die Implantate von den sehr kurzen, nahezu komplett den Schenkelhals erhaltenden Systemen bis hin zu Prothesen, bei denen nur der distalste Teil von Standardprothesen gekürzt wurde. Eine in der Literatur mehrfach zitierte Klassifikation empfiehlt die Osteotomiehöhe als diskriminierenden Faktor. Diese unterscheidet in schenkelhalserhaltende, schenkelhalsteilerhaltende und schenkelhalsresezierende Kurzschäfte.
Keywords: primary hip arthroplasty; short stemmed endoprosthesis; hip arthroplasty classifications; biomechanics